Copper and Caribou Inuit skin clothing production - Oakes, Jill E. (Jill Elizabeth), 1952- (Book collections on Project MUSE., 1991)
This study of caribou skin clothing made by Inuit seamstresses in Coppermine, Bathurst Inlet, Cambridge Bay and Arviat, Northwest Territories, includes information collected from seamstresses as the author constructed skin clothing under their direction, and a comparison of garments made by Copper and Caribou Inuit as well as by Paallirmiut and Ahiarmiut groups. The text includes numerous clothing patterns, for parkas, mittens, stockings, pants anboots, a list of Inuit clothing terminology, an extensive bibliography and a map.